Pengaruh Sudut Punch dan Ketebalan Pelat terhadap Springback pada Bending V - Rusdi Nur; Muhammad Arsyad Suyuti; Muh Reza B; Misbahuddin Misbahuddin (Politeknik Negeri Ujung Pandang, 2019)
The bent plate is inseparable from the phenomenon that determines the size of the resulting bending angle. This phenomenon is called springback. Springback is a condition that occurs on a sheet plate when bending is done where after the punch load is removed the bent sheet plate has a tendency to return to its original form. Mini brake bending V tool with a hydraulic jack system produces springback of 1-5 degrees for punch angle 85 ° radius 2.5 mm and carbon steel material St 42 at thickness 3, 4 and 5 mm. Therefore, this study was conducted to find out how the influence of punch angle and plate thickness on springback. The limitation problem in this study is the thickness of the plates used 2 and 4 mm. The type of method used is bending V bottoming with a die angle of 90 °, the punch angle used is 80, 85, and 90, the punch radius used is 2, 4 and 6 mm, and the plate material used is carbon steel. The research method starts from designing die set, punch and die test aids, and making test specimens, then bending test, bending angle and springback measurements are carried out. Based on the research conducted, the greater the punch angle, the smaller springback produced and the thicker the plate, the smaller springback produced tends to be smaller, where the smallest springback is obtained on a plate thickness of 6 mm with a punch angle of 90 ° 4 mm radius obtained -0.31o.